The reasons for the different nest shapes of Megapis bees - Woyke Jerzy; Wilde Jerzy; Wilde Maria (Journal of Apicultural Science, 2016)
Over a 37-year period, we observed 1011 active bee nests and abandoned combs of Apis dorsata and Apis laboriosa in Nepal, India, the Philippines, and Bhutan. This article focuses on the reasons for the different shapes of the nests. We discovered that differing ambient conditions were the reasons for the following three shapes of symmetrical nests: vertical semi-ellipse, semicircle, and the horizontal semi-ellipse. We noted that asymmetrical nests were constructed when there was lack of space to extend the comb equally in both external directions. An asymmetrical nest also appeared when remnants of a previous comb remained on one edge of the nest. Convex nests were constructed to avoid excess sun exposure. Concave nests appeared as a result of low temperatures during the night and part of the day (Nepal). An L-shape nest was constructed when there was lack of space available to extend the nest in a straight direction. The shape of the nests also determines the way the combs fall.